2014
DOI: 10.1186/1477-7819-12-344
|View full text |Cite
|
Sign up to set email alerts
|

Factors responsible for long-term survival in metastatic breast cancer

Abstract: BackgroundAlthough survival of patients with metastatic breast cancer (MBC) has been significantly prolonged over the past decade due to improvement of anti-cancer therapeutics, only a few patients survive for more than 10 years. It has not been determined which patients can have long-term survival with treatment.MethodsTo determine prognostic factors responsible for long-term survival, we retrospectively compared clinicopathologic factors of patients with MBC who survived for 50 months or more after diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…The deleterious effects of cancer are not limited to the primary tumor itself, as evidenced by the sentinel lymph node's role in tumor immune suppression [3, 9] as well as the high number of cancer-associated complications and mortalities associated with both metastasis [25, 26] and thrombosis [27, 28]. Distant intercellular signaling can occur even prior to metastasis to precipitate such effects, for example via remodeling of sentinel lymph nodes [29], VEGFR1 + haematopoietic progenitor cell recruitment to pre-metastatic niches [14], and secretion of tumor-derived pro-coagulants and cytokines driving thrombosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious effects of cancer are not limited to the primary tumor itself, as evidenced by the sentinel lymph node's role in tumor immune suppression [3, 9] as well as the high number of cancer-associated complications and mortalities associated with both metastasis [25, 26] and thrombosis [27, 28]. Distant intercellular signaling can occur even prior to metastasis to precipitate such effects, for example via remodeling of sentinel lymph nodes [29], VEGFR1 + haematopoietic progenitor cell recruitment to pre-metastatic niches [14], and secretion of tumor-derived pro-coagulants and cytokines driving thrombosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Metronomic chemotherapy, which is defined as continuous or frequent treatment with low doses of anticancer agents, has been reported to result in favorable tumor responses and prolonged survival (13). We previously reported that the proportion of patients who received a metronomic regimen as the most effective regimen was two-thirds of the long-term survivors (65.3%), who survived for ≥50 months after diagnosis with MBC, which was double that of the non-long-term survivors, who succumbed to the disease within 50 months (12). The mechanisms of inhibition of tumor growth by metronomic chemotherapy remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that more MBC patients who survived for ≥60 months following MBC diagnosis had received metronomic chemotherapy, compared with patients exhibiting shorter survival (12). Metronomic chemotherapy, which is defined as continuous or frequent treatment with low doses of anticancer agents, is commonly used as palliative care in patients who have been heavily pretreated with cytotoxic drugs or who have poor performance status (13).…”
Section: Introductionmentioning
confidence: 99%
“…A large group of patients might have a prolonged survival after the diagnosis of advanced disease. [47][48][49] In such circumstances, one could consider a therapeutic strategy with a low toxi city profile, good tumour control and economically viable for the healthcare system. Moreover, management of metastatic disease must be driven by multiple considerations that include not only the heterogeneity of breast cancer subtypes, but also the heterogeneity of breast cancer patients, such as patient age, preferences, frailty, co-morbidities and potential contraindications to more-intensive regimens.…”
Section: Ideal Agents and Drug Repositioningmentioning
confidence: 99%